Beyond traditional water splitting for energy-efficient waste-to-hydrogen conversion with an inorganic–carbon hybrid nanosheet electrocatalyst. Issue 9 (4th January 2021) - Li, Yapeng; Wang, Yixuan; Liu, Yi; Qian, Qizhu; Li, Ziyun; Mu, Yang; Zhang, Genqiang
Abstract : The waste-to-hydrogen system has been demonstrated with the RuP2 -carbon hybrid nanosheets as the cathode electrocatalyst of microbial electrolysis cell, which merely needs 0.18 V to generate hydrogen, far below than the traditional water electrolysis. Abstract : Here, we reported an inorganic–carbon hybrid nanosheet that possesses remarkable hydrogen evolution activity (26 mV@10 mA cm −2 ) in 1.0 M PBS by coupling RuP2 nanoparticles with N, P co-doped carbon (RP-HNS), delivering a decent energy yield of ∼330% and a remarkable overall energy recovery of 81.4% for H2 production in the waste-to-hydrogen conversion system when used as a microbial electrolysis cell cathode.